PH-sensitive nanoparticles for improved oral delivery of dapsone: risk assessment, design, optimization and characterization. (August 2017) - Chaves, Luíse L; Costa Lima, Sofia A; Vieira, Alexandre CC; Barreiros, Luísa; Segundo, Marcela A; Ferreira, Domingos; Sarmento, Bruno; Reis, Salette
Aim: To optimize the production of pH-sensitive dapsone (DAP) nanoparticles based on Eugradit L100 (NPs-EL100-DAP) for oral delivery.Materials & methods: NPs-EL100-DAP were optimized using a Plackett–Burman design and a Box-Behnken design. The physicochemical properties of the obtained nanoparticles were monitored by microscopy, dynamic light scattering, Fourier transform infrared spectroscopy, differential scanning calorimetry, in vitro release assays, and examined for cytotoxicity and permeation across intestinal barrier.Results: The in vitro release assay of NPs-EL100-DAP confirmed the nanoparticles' pH sensitivity and the ability to deliver DAP at intestinal environment. NPs-EL100-DAP demonstrated enhanced intestinal interactions in comparison to free DAP, across Caco-2 monolayers.Conclusion: These studies demonstrate the potential of NPs-EL100-DAP as a therapeutic platform for oral treatment of leprosy.